APAKAH PENGUNGKAPAN KEBERLANJUTAN DAN PELAPORAN TERINTEGRASI DAPAT MENURUNKAN RISIKO IDIOSINKRATIK? - Firmansyah, Amrie; Pua Geno, Muchamad Rizal; Pamungkas, Pria Aji; Fauzi, Irfan; Bachtiar, Muchamad Izaaz Hannun (Ultimaccounting Jurnal Ilmu Akuntansi, 2023)
Abstract - Risk is something that most investors encounter when investing. Idiosyncratic risk is a risk that can be controlled and diversified to lessen it. Idiosyncratic risks arise due to internal firm conditions, which can stem from manager policies. This study aims to investigate the impact of sustainability disclosure and integrated reporting on idiosyncratic risks. This quantitative study uses research data from the financial reports of manufacturing businesses listed on the IDX between 2016 and 2020, found at www.idx.co.id. This study also makes use of data from www.financial.yahoo.com. Furthermore, this study uses monthly data on 10-year government bond yields from www.bloomberg.com. Purposive sampling was used to select 555 observations (firm-year) for this study. According to this study, sustainability disclosure has a beneficial influence on idiosyncratic risk when utilizing both the market and Fama-French models. Using the Fama-French model, this study discovered that integrated reporting had a favorable influence on idiosyncratic risk. Integrated reporting, on the other hand, has no influence on idiosyncratic risk when utilizing the market model. This study extends capital market-based financial accounting research by using non-financial data and information essential in making investment decisions in addition to financial report figures. Keywords: Disclosure; Investment; Non-Financial; Non-Systematic Risk